Dakwah Ekonomi (Pengaruh Penerapan Sistem Verifikasi Legalitas Kayu ( SVLK ) Terhadap Industri Furniture di Jepara , Jawa Tengah) - Ansori, Miswan; Wahyudin, Aan (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2018)
The Timber Legality Verification System (SVLK) is one of the emerging government initiatives to tackle illegal logging and promote legal timber in Indonesia to International Country. The system aims to ensure that timber and wood products produced in Indonesia come from verifiable legal sources. SVLK is implemented through certification mechanism by independent party (Wood Legality Verification Institution / LVLK) which has been accredited by National Accreditation Committee. The purpose of this study is to find out how the influence of the implementation of government rules on the obligation to have SVLK against companies that export wooden furniture products in Jepara. This study will use 30 companies engaged in the export of Wood Furniture to foreign countries who entered as members of the Indonesian Furniture and Handicraft Association (HIMKI) Jepara Raya, Central Java. The results of this study will be forwarded to stakeholders related to SVLK implementation obligations in the furniture industry,whether the policy has a positive or negative impact on furniture industry exports in Jepara This research is descriptive and qualitative. Data collection methods were conducted using field research with interviews and some questioner to obtain primary and secondary data, observation, and literature.